2019
DOI: 10.1088/1755-1315/315/7/072037
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of cyproconazole and fludioxonil for plant protection against the phytopathogenic fungus Botrytis cinerea

Abstract: The effect of two active ingredients of fungicides on pure culture of Botrytis cinerea Pers was assessed. The analysis was carried out for 16 possible combinations of cyproconazole and fludioxanil, one of which was a control one. According to the results of measurements of the dry weight of mycelium in an accumulative culture, a diagram was constructed and two-factor analysis of variance was given. It has been established that the combined effect of these fungicides has a significant effect on the growth of my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Table (1) and figure (5 A) in this study showed the genotoxic potential of CPZ on adrenal gland cells, as well as the protective impact of fennel oil. This genotoxic impact was proved as an increase with statistical significance (P ≤ 0.05) in the proportion of comet-tail DNA in the nuclei of adrenal gland cells.…”
Section: Comet Assaysupporting
confidence: 57%
See 2 more Smart Citations
“…Table (1) and figure (5 A) in this study showed the genotoxic potential of CPZ on adrenal gland cells, as well as the protective impact of fennel oil. This genotoxic impact was proved as an increase with statistical significance (P ≤ 0.05) in the proportion of comet-tail DNA in the nuclei of adrenal gland cells.…”
Section: Comet Assaysupporting
confidence: 57%
“…Triazoles have rapidly become some of the most profitable and commonly used fungicides in the world due to their efficacy in treating a variety of fungal infections in plant crops and vegetables. CPZ is one of these triazoles that is widely used across the world (1) . However, the experimental findings in non-target species demonstrate a variety of undesirable toxic effects of triazoles on organisms, including oxidative stress and endocrine disruption (2) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that many fungicides, in addition to the protective effect, have a toxic effect both independently [20] and indirectly, through the effect on the production of mycotoxins. Consequently, fungicides can be, on the one hand, in themselves toxic to plants, and on the other hand, they can contribute to the production of toxins by the fungus.…”
Section: Introductionmentioning
confidence: 99%